Kai-Xin-San ameliorates mild cognitive impairment in SAMP8 mice by inhibiting neuroinflammation and pyroptosis via NLRP3/Caspase-1 pathway modulation - Liu, Shu; Song, Xiaochen; Sun, Yuefeng; Sun, Ailin; Li, Yang; Li, Yuyu; Chen, Jing (Frontiers in Pharmacology, 2025)
Mild Cognitive Impairment (MCI) represents a critical stage between normal aging and dementia, with limited effective interventions currently available. This study investigated the effects of Kai-Xin-San (KXS), a traditional Chinese herbal formula, on cognitive function, neuroinflammation, and pyroptosis in a senescence-accelerated prone 8 (SAMP8) mouse model of MCI. SAMP8 mice were treated with KXS for 8 weeks, followed by behavioral tests, biochemical analyses, and histological examinations. KXS significantly improved spatial memory, working memory, and executive function in SAMP8 mice. Furthermore, KXS treatment reduced β-amyloid (Aβ) deposition, attenuated neuroinflammation by decreasing pro-inflammatory cytokine levels (IL-1β, IL-18, IL-6, TNF-α), and inhibited microglia activation in the hippocampus. Notably, KXS suppressed pyroptosis by modulating the NLRP3/Caspase-1 signaling pathway, as evidenced by reduced expression of NLRP3, ASC, Caspase-1, and GSDMD. These effects were abolished by treatment with the NLRP3 inflammasome agonist Nigericin, suggesting that NLRP3 inhibition is a key mechanism of KXS action. Our findings reveal a novel mechanism by which KXS exerts neuroprotective effects in MCI, simultaneously targeting Aβ accumulation, neuroinflammation, and pyroptosis. This multi-target approach of KXS highlights its potential as a therapeutic strategy for MCI and warrants further investigation in clinical settings.